2017
DOI: 10.1161/circulationaha.117.027402
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Midterm Cardiac Remodeling After Surgical Pulmonary Valve Replacement in Adults With Repaired Tetralogy of Fallot

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(54 citation statements)
references
References 33 publications
7
45
0
2
Order By: Relevance
“…This is in accordance with a recent trend towards interventions when patients are either asymptomatic or mildly symptomatic to minimise peri-procedural risks and improve prognosis. For example, percutaneous pulmonary valve implantation late after repair of tetralogy of Fallot is currently being performed on patients with severe pulmonary regurgitation and progressive right ventricular dilatation, irrespective of symptoms, to optimise right ventricular remodelling and long-term prognosis 14. Indeed, in our study only 26.8% of patients were symptomatic at the time of catheter intervention.…”
Section: Discussionmentioning
confidence: 78%
“…This is in accordance with a recent trend towards interventions when patients are either asymptomatic or mildly symptomatic to minimise peri-procedural risks and improve prognosis. For example, percutaneous pulmonary valve implantation late after repair of tetralogy of Fallot is currently being performed on patients with severe pulmonary regurgitation and progressive right ventricular dilatation, irrespective of symptoms, to optimise right ventricular remodelling and long-term prognosis 14. Indeed, in our study only 26.8% of patients were symptomatic at the time of catheter intervention.…”
Section: Discussionmentioning
confidence: 78%
“…Table 1 summarizes the selected clinical applications of 4D flow MRI in various vascular fields. Past studies have also demonstrated hemodynamics of normal cohorts, various hemodynamic changes in cardiovascular diseases, and comparisons before and after interventions for cardiovascular diseases [26,41,52,53]. This article focuses on the clinical application of 4D flow MRI in the field of the great arteries, including aortic diseases, adult congenital heart diseases (CHDs), and pulmonary hypertension.…”
Section: Clinical Application Of 4d Flow Mrimentioning
confidence: 99%
“…When the ventricle becomes decompensated, excessive right ventricular dilatation with deteriorated function, arrhythmia, and premature death can be induced. CMR can be used to stratify the risk and surgical intervention of repaired TOF with right heart failure [52,72,73]. In clinical practice, the proposed indications of pulmonary valve replacement in asymptomatic patients based on CMR findings include RV end-diastolic volume index >150 mL/m 2 , RV end-systolic volume index >80 mL/m 2 , RV ejection fraction (EF) <47%, and left ventricular (LV) EF <55% [73].…”
Section: Repaired Tetralogy Of Fallotmentioning
confidence: 99%
“…We thank the authors for their interest in our recent publication in which we reported on significant right heart structural reverse remodelling seen in the immediate post-surgical pulmonary valve replacement (PVR) period in patients with repaired Tetralogy of Fallot (rTOF), which was followed by further time-related biological remodelling exemplified by further reduction in RVESVi. 1 Patients put forth for PVR following multidisciplinary review were opportunistically and serially approached by the research team (SVB-N) for study inclusion if they fulfilled the study inclusion criteria. The study cohort patients did not differ from the rest of the patients with TOF undergoing surgical PVR during this period in terms of clinically relevant co-variates of age, gender, symptomatology, QRS duration on ECG as well as biventricular volumes and function as assessed by CMR.…”
Section: I S C L a I M E R : T H E M A N U S C R I P T A N D I T S mentioning
confidence: 99%
“…The relevant data illustrating this is presented in Supplementary Table 3, online supplement. 1 We acknowledge that specific right ventricular (RV) volumetric thresholds (RVEDVi≥150ml/m 2 , RVESVi≥80ml/m 2 ) were being gradually adopted for asymptomatic patients during the study period, which may have influenced the timing of PVRs and therefore limit the applicability of our results to patients with severely dilated RVs at the extremes of the volumetric spectrum. We had therefore compared the study patients to nonstudy TOF patients undergoing PVR in Supplementary Table 3 and showed that there was no evidence of excluding patients at volumetric extremes.…”
Section: I S C L a I M E R : T H E M A N U S C R I P T A N D I T S mentioning
confidence: 99%